Analisis Pembentukan Karakter : Peran Guru Dalam Meningkatan Kemandirian Pada Anak Usia Dini - Munawarah; Raden Rachmy Diana; Suminah; Isnawati (Lembaga Swadaya Masyarakat Asosiasi Masyarakat Madani Indonesia (AMMI), 2024)
Increasing children's independence requires significant attention from adults, including teachers and parents. instilling independent character in children requires various stimulations that can support the formation of independence in children from an early age. This type of research is library research or library research. Sources of data in this study came from reviewing articles, journals, books and research results that could answer the formulation of the problem in this study. The data analysis technique in this study is data reduction, displaying the data and proceeding with outlining the conclusions. The results showed that the teacher's role in increasing children's independence was obtained from the competencies possessed by the teacher, namely pedagogic, professional, personality and social competencies. Stimulation in increasing children's independence can be obtained from routine habituation activities including 1) putting their own shoes in their place, tidying up their own cutlery, putting books and toys back in their place, Duha prayer, and toilet training. In structured habituation activities, children will be guided by the teacher according to the planning and implementation according to the theme of the activities in the Daily Learning Implementation Plan. Then the formation of independence in children can be supported by learning media, namely visual, audio and audio-visual media.